Effects of injection parameters on propagation patterns of hydrogen-fueled rotating detonation waves. (15th November 2022) - Yao, Kepeng; Yang, Pengfei; Teng, Honghui; Chen, Zheng; Wang, Chun
Abstract: Two-dimensional rotating detonation waves (RDWs) with separate injections of hydrogen and air are simulated using the Navier–Stokes equations together with a detailed chemical mechanism. The effects of injection stagnation temperature and slot width on the detonation propagation patterns are investigated. Results find that extremely high temperatures can lead to a chaotic mode in which detonation waves are generated and extinguished randomly. Increasing the slot width can reduce the number of detonation waves and finally trigger detonation quenching at a low injection stagnation temperature. But increasing the slot width can change the RDW propagation pattern from a chaotic to a stable mode under high injection temperature. Furthermore, the kinetic parameter τ (representing the chemical reactivity of the mixture) and the kinematic parameter α (representing the mixing efficiency of hydrogen and oxygen) are introduced to distinguish the RDW propagation patterns. Graphical abstract: Image 1 Highlights: The effect of injection on rotating detonation waves is quantitatively displayed. Increasing slot width can lead to the detonation propagation patterns stably. Increasing injection stagnation temperature may lead to a chaotic mode. Two parameters are proposed to distinguish the detonation propagation patterns.